Posterior polymorphous dystrophy – changes in corneal morphology in confocal microscopy - Szaflik, Jacek P.; Kołodziejska, Urszula; Udziela, Monika; Kołodziejczyk, Wojciech; Szaflik, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To describe the in vivo confocal microscopic findings in posterior polymorphous dystrophy (PPD). Material and methods: Eleven patients (22 eyes) with PPD suspected or clinically diagnosed were examined using scanning slit white light confocal microscopy (ConfoScan 3, Nidek Technologies). Results: Endothelial cell densities ranged from 716 to 2380 cells/mm2 and endothelial polymegathism was noted in all cases. In 5 cases PPD changes was reported unilateral. Confocal microscopy demonstrated a variety of vesicular and linear abnormalities. In 13 eyes exhibited bright, nucleus-like structures within endothelial cells. Stromal edema was noted in 4 cases. Conclusions: To our knowledge, we present the largest case series of PPD imaged by in vivo confocal microscopy. Confocal microscopy images of PPD are very characteristic. This method allows to confirm presumptive or to identify final diagnosis. Our study enhances the value of confocal microscopy in detection and monitoring corneal abnormalities.